Distinguishing Hattatsu, Shinpo, and Jotatsu: A Semantic Component and Contextual Usage Analysis of Japanese Synonymous Verbs - I Wayan Wahyu Cipta Widiastika; Ni Wayan Meidariani; Made Henra Dwikarmawan Sudipa (Bale Literasi: Lembaga Riset, Pelatihan & Edukasi, Sosial, Publikasi, 2026)
This study investigates the semantic distinctions and contextual usage of three Japanese verbs associated with the concept of development, namely hattatsu, shinpo, and joutatsu, from the perspective of lexical semantics. Although these verbs are often translated into English as “development,” “progress,” or “improvement,” each carries distinct semantic characteristics and is used in different contexts. The data consist of example sentences illustrating various types of development, including physical, cognitive, technological, and skill-related development. The findings indicate that hattatsu primarily denotes natural and gradual development, commonly associated with physical growth, biological processes, or functional advancement. In contrast, shinpo refers to progressive advancement or positive change on a broader scale, particularly in fields such as science, technology, and society, often implying innovation and significant achievement. Meanwhile, joutatsu specifically describes the improvement of an individual’s abilities through continuous practice, learning, and experience, emphasizing a deliberate and effort-driven process.The analysis demonstrates that, despite sharing a general meaning related to development, these verbs differ substantially in their semantic components and contextual distributions. Understanding these distinctions is essential for the accurate and appropriate use of Japanese in academic, educational, and everyday communication. Furthermore, this study contributes to lexical semantic research by clarifying subtle meaning differences among near-synonymous verbs and offers practical insights for Japanese language learners, educators, translators, and lexicographers. The findings may also help reduce the misuse of semantically related expressions and support more precise language instruction and dictionary descriptions.